The Role of Customary Leaders in Supporting the Duties of Bhabinkamtibmas in Resolving Legal Conflicts in Southwest Papua - Saed Bil Aswar Husaeni; Surahman Amin; Syahrul; Udin Latif; Hujriman (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study examines the role of customary leaders in supporting Bhabinkamtibmas in resolving village-level conflicts in Southwest Papua, Indonesia. Employing a qualitative socio-legal approach, the study draws on in-depth interviews with customary leaders, local government officials, and migrant community members in Sorong Regency and Sorong City. Guided by legal pluralism, hybrid governance, and community policing perspectives, the findings reveal that conflict resolution operates through a hybrid legal order in which customary and state institutions interact through cooperation, mutual recognition, and negotiated authority rather than hierarchical substitution. Customary leaders function as primary actors in restorative dispute resolution, deriving legitimacy from community trust, kinship networks, and communal consensus, while Bhabinkamtibmas strengthen procedural legitimacy and facilitate coordination between customary and formal institutions. The study advances the concept of negotiated legitimacy to explain how customary and state actors continuously construct authority, accountability, and social acceptance within legally plural governance systems. The findings demonstrate that effective community policing in indigenous societies depends on collaboration with locally legitimate institutions and that sustainable conflict resolution emerges through culturally responsive governance arrangements that reconcile customary authority with procedural accountability.